Avaliação do comportamento mecânico, térmico, magnético, e microestrutural, de uma liga Heusler CuAlMnTiB submetida a diferentes temperaturas de têmperas - Almeida, Gabriely Medeiros de Souza Falcão de (2023)
CuAlMn alloys exhibit excellent characteristics that make them very promising for magnetic applications. The numerous properties, depend on martensitic phase transformations, thermoelastic transformations and magnetic transitions. The alloy used in this work, has four ingots with the same elements in the same proportions, Cu - 23.69 at.% Al - 15.51 at.% Mn - 0.48 at.% Ti - 0.39 at.% B, varying only the tempering temperature. Homogenization of the alloy was done by varying three samples by 50 °C in quenching temperature and one sample was left under raw melt conditions. To evaluate the influence of the solubilization temperature on the studied alloy, the characterizations of Optical Microscopy, X-ray Diffraction, Vickers Microhardness, Differential Scanning Calorimetry and Vibrating Sample Magnetometer were performed. That showed us that increasing the solubilization temperature caused an increase in grain size for the tempered samples and a reduction in the relative fraction of the ferromagnetic L21(f) phase. The samples have a preferential orientation in the (220) direction and the presence of the peaks (111) and (200) provide evidence for the presence of the ferromagnetic phase. The microhardness behavior is in accordance with the known Hall-Petch relationship, reducing with increasing grain size. The calorimetry test showed that the heat treatment hinders the transformation from ferromagnetic to paramagnetic phase and facilitates the inverse transformation. Hysteresis curves proved ferromagnetic ordering for all samples. The saturation magnetization values were lower in the samples of solubilization temperature above 750°C. The values of coercive field and remaining magnetization decreased with increasing solubilization temperature.